Sublime, Grotesque and Caricature in the Verse Texts of Poets of the Slovenian Moderna Period - Kusterle, Jernej (Slavia Centralis, 2024)
The paper will first briefly present the sublime, grotesque and caricature in their historical contexts and with the most key philosophical ideas. All three phenomena are indeed interrelated: they are characterized by containing both beauty and ugliness, whereby in the case of the sublime, beauty appears as the dominant underlying feature, to which ugliness adds a negative semantic background; while in the case of the grotesque and caricature, the given dominant appears to be ugliness, which is mitigated by the presence of the beautiful. The latter is what contributes to the reduction of the recipient’s extreme resistance. Later in the paper, all three concepts will be applied to some typical examples of verse texts of poets of the Slovenian Moderna Period.